Essential and dual effects of Notch activity on a natural transdifferentiation event - Thomas Daniele; Jeanne Cury; Marie-Charlotte Morin; Arnaud Ahier; Davide Isaia; Sophie Jarriault (Nature Communications)
Abstract Cell identity can be reprogrammed, naturally or experimentally, albeit with low frequency. Why some cells, but not their neighbours, undergo a cell identity conversion remains unclear. We find that Notch signalling plays a key role to promote natural transdifferentiation in C. elegans hermaphrodites. Endogenous Notch signalling endows a cell with the competence to transdifferentiate by promoting plasticity factors expression (hlh-16/Olig and sem-4/Sall). Strikingly, ectopic Notch can trigger additional transdifferentiation in vivo. However, Notch signalling can both promote and block transdifferentiation depending on its activation timing. Notch only promotes transdifferentiation during an early precise window of opportunity and signal duration must be tightly controlled in time. Our findings emphasise the importance of temporality and dynamics of the underlying molecular events preceding the initiation of natural cell reprogramming. Finally, our results support a model where both an extrinsic signal and the intrinsic cellular context combine to empower a cell with the competence to transdifferentiate.